Queen and the crown [videorecording (DVD)] - Bextor, Robin; Bextor, Robin; Dupont, Nigel; Foote, Stephen (Reel 2 Reel Films, 2022)
A feature length tribute to Her Majesty Queen Elizabeth II, the UK's longest reigning monarch, from her birth in London on April 21st 1926 to the nationwide outpouring of gratitude and thanks to Her Majesty in June 2022 marking the Platinum Jubilee, and then the sorrow just weeks later and her historic and epic funeral. Following the course of her life as shock of the abdication in 1936 catapulted her father unexpectedly onto the throne, suddenly making her the young princess heir to the crown, we see the way she pledged to give herself entirely to serving the nation, how her parents prepared her and how she learned to make hard decisions, always putting the country and its people first. Enlisting a number of royal experts and historians, including palace insiders who worked in the service of her majesty, we discover the highs and lows of her reign and the pressures that the crown brings.